Strategi Tax Planning dalam Meningkatkan Efisiensi Beban Pajak pada Perusahaan Manufaktur: Studi Kasus CV Maju Jaya Furniture - Andini Regina Putri; Jhosep Dodikarlov; Reva Liafahni; Rintan Dwi Astuti; Sandi Nasrudin Wibowo (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
The growth of Micro, Small, and Medium Enterprises (MSMEs) in the furniture industry has increased significantly, yet many businesses continue to face challenges in fulfilling their tax obligations due to limited knowledge of tax regulations, inadequate transaction records, and inefficient Tax Planning. This study aims to analyze the Income Tax (PPh) and Value-Added Tax (PPN) obligations of CV Maju Jaya Furniture and formulate Tax Planning strategies to improve tax efficiency in accordance with applicable regulations. A case study approach was employed using the company’s financial data, including sales, operating expenses, employee salaries, and fixed assets. The data were analyzed descriptively through tax calculations and simulations of Tax Planning strategies. The results indicate that the company had a final Income Tax liability of Rp19,000,000 and an underpaid Value-Added Tax of Rp253,000,000. After optimizing fixed asset depreciation, providing tax allowances to employees, and scheduling purchases from Taxable Business suppliers, the VAT underpayment decreased to Rp233,000,000, generating tax savings of Rp20,000,000. These findings demonstrate that appropriate Tax Planning can improve tax efficiency while complying with prevailing tax regulations and provide practical guidance for MSMEs in managing their tax obligations.